Mathematical Modelling of RF Plasma Flow at Low Pressures with 3D Electromagnetic Field - A. Yu Shemakhin; V. S. Zheltukhin (Advances in Materials Science and Engineering)
In this study, a hybrid mathematical model of a low-pressure RF plasma jet in transition mode between continuum and free molecular flow at a Knudsen number of 8·10−3 ≤ Kn ≤ 7·10−2 for a carrying gas is described. The model takes electrons, ions, metastable atoms, and potential and curl electromagnetic fields into account. The model is based on both a statistical approach for the atoms in the ground state and a continuum model for other components. The results of plasma flow calculations in an undisturbed jet are described. The distributions of the electrodynamic and electrostatic parts of the electric field are given. It has been observed that the plasma jet has a layered structure along the stream: a positive charge region is formed at the beginning of the jet, followed by a negative charge region, and then a positive one again. The reason for the formation of a layered structure is the fast flow expansion when the plasma inflows into the vacuum and the difference in electron and ion pulse.